2003
DOI: 10.1016/s1097-2765(03)00454-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of SMRT Corepressor Recruitment by the BCL6 BTB Domain

Abstract: BCL6 encodes a transcription factor that represses genes necessary for the terminal differentiation of lymphocytes within germinal centers, and the misregulated expression of this factor is strongly implicated in several types of B cell lymphoma. The homodimeric BTB domain of BCL6 (also known as the POZ domain) is required for the repression activity of the protein and interacts directly with the SMRT and N-CoR corepressors that are found within large multiprotein histone deacetylase-containing complexes. We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
401
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 262 publications
(421 citation statements)
references
References 58 publications
14
401
0
Order By: Relevance
“…Nevertheless, as discussed above, BCL6 autoregulation and differentiation-coupled control of PRDM1 expression offer two excellent model systems in which mechanistic details of BCL6-mediated transcription inhibition can be investigated in the future. Structural studies of the interaction between BCL6 and the lateral groove corepressors suggest that each BCL6 dimer can potentially bind to two such corepressors (SMRT, NCoR, and BCoR) at a time (1). Since our data indicate that BCL6 binds to CtBP1 primarily through the POZ domain with a minor contribution from RDII, it raises the question whether a BCL6 dimer already in complex with CtBP can further engage one or more of the lateral groove corepressors (which are very large proteins) and/or the RDII corepressors (HDAC2 or MTA3/NuRD) and vice versa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, as discussed above, BCL6 autoregulation and differentiation-coupled control of PRDM1 expression offer two excellent model systems in which mechanistic details of BCL6-mediated transcription inhibition can be investigated in the future. Structural studies of the interaction between BCL6 and the lateral groove corepressors suggest that each BCL6 dimer can potentially bind to two such corepressors (SMRT, NCoR, and BCoR) at a time (1). Since our data indicate that BCL6 binds to CtBP1 primarily through the POZ domain with a minor contribution from RDII, it raises the question whether a BCL6 dimer already in complex with CtBP can further engage one or more of the lateral groove corepressors (which are very large proteins) and/or the RDII corepressors (HDAC2 or MTA3/NuRD) and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Among the corepressors with well-documented in vivo functions, nuclear receptor coreceptor (NCoR), silencing mediator for retinoid and thyroid hormone receptors (SMRT), and BCL6 corepressor (BCoR) are recruited through the POZ/BTB domain while the central RDII region can interact with histone deacetylase 2 (HDAC2) and MTA3, which is a cell-type-specific component of the Mi-2/NuRD complex (8, 13-15, 19, 20, 24, 27, 49). Structural studies revealed that SMRT, NCoR, and BCoR all bind to a lateral groove in the POZ domain through a stretch of 17 amino acids (1). Using a cell-permeable BCL6 peptide inhibitor, BPI, designed to block POZ lateral groove corepressor recruitment, we have shown that SMRT/NCoR/BCoR control cell proliferation and survival in GC-derived B cells by mediating BCL6-dependent repression of genes such as ATR, TP53, and CDKN1A (32,35,37).…”
mentioning
confidence: 98%
“…Transcription factors with a BTB domain at the N-terminus comprise a large important class of molecules involved in development and carcinogenesis. As shown in crystallographic studies, the BTB domains from PLZF (promyelocytic leukemia zinc finger), 2,3 BCL6, 4,5 LRF/ZBTB7, 6,7 Bach1, 8 and FAZF 9 are tightly interwound homodimers. In the case of Miz1, there are contradicting crystallographic data that BTB exists as either homodimer 9 or homotetramer.…”
Section: Introductionmentioning
confidence: 89%
“…[23][24][25][26] As controls, we used wellcharacterized BTB domains of human proteins Bcl6 and Miz1, which can form dimers 4 and tetramers, 10 respectively. We also examined the BTB domain of CP190, which has no significant homology to BTBs from the ttk group, and BTB from a vertebrate homolog of GAF identified recently.…”
Section: Btb Domains Of Gaf and Several Other Transcriptional Factorsmentioning
confidence: 99%
“…Both the BTB and RD2 domain recruit distinct sets of co-repressors (Figure 1). The BCL6 BTB domain forms an obligate homodimer to create two identical and symmetrical extended lateral grooves that form docking sites for the co-repressor proteins SMRT (silencing mediator of retinoid and thyroid receptor), NCOR(nuclear receptor corepressor) and BCOR (BCL6 corepressor) (Figure 1) [36,37]. NCOR and SMRT are highly conserved scaffold/adaptor proteins, both of which can individually form a stable complex with HDAC3 (histone deacetylase 3), TBL1 (transducin-beta-like protein 1), TBLR1 (transducin-beta-like related protein 1) and GPS2 (G protein pathway suppressor 2) [38].…”
Section: Biochemical Mechanisms Of Action Of Bcl6mentioning
confidence: 99%